Enhancing Students' English Language Skills through Active Learning at an Islamic University - Rio Febriannur Rachman (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
English is the most widely used international language in the world. Mastering English skills in this modern era is, therefore, crucial. Consequently, English needs to be sufficiently taught to students of all educational levels. In response to the issue, this study aims to investigate the active learning strategy (intense involvement of students in learning processes) employed in the Faculty of Islamic Da'wah and Communication at an Islamic Institute in Lumajang, East Java. This study was designed as a case study with in-depth interviews and observations as the main data collection. The results of this study indicate that although the active learning method was successfully implemented in this faculty, the strategies and learning activities should be varied.